Current patterns of pharmacological treatment for coronary heart disease based on the Russian cohort of the hospital arm of the EUROASPIRE V survey. (14th October 2021) - Pogosova, N; Boytsov, S A; Ausheva, A K; Sokolova, O Y; Pozdnyakov, Y M; Salbieva, A O; Karpova, A V; Yusubova, A I; Arutyunov, A A
Abstract: Background: Several drug classes have shown their ability to improve risk factors control and prognosis in coronary heart disease (CHD). Therefore, it is important to monitor the prescription patterns on a regular basis to ensure that all the eligible patients receive the potentially lifesaving medications. Purpose: To describe prescription and uptake of main guideline-recommended drug classes in men and women with history of acute coronary syndromes (ACS) or cardiac revascularization enrolled into the hospital care arm of EUROASPIRE V (European Action on Secondary and Primary Prevention by Intervention to Reduce Events) study in Russian centers vs the whole study population. Methods: The hospital arm of EUROASPIRE V was a cross sectional survey covering multiple European countries including Russia. Within each country one or more hospitals were selected where consecutive pts (both genders, ≥18 and <80 years of age) hospitalized for myocardial revascularization procedures or for ACS were retrospectively identified. Identified patients were invited for interview, which had to take place ≥6 months and <2 years after the index hospitalization. Pharmacological treatment was assessed based on the prescriptions in the discharge letters and during the interview. Results: A total of 399 pts (women, 27.1%) have been interviewed in Russia vs 8261 pts (women, 25.8%) in the whole survey. The mean age of the Russian cohort at interview was 62.8±8.7 years in Russia vs 63.6±9.6 years in all EUROASPIRE V pts. The table below represents the proportion of pts prescribed and actually receiving main drug classes. Both in the Russian cohort and in the whole study population the proportion of patients receiving essential drug classes didn't differ much by gender. In Russian centers, 95.9% of men and 91.7% of women received antiplatelets (vs 92.8% and 91.8%, respectively, in the whole study population). For statins the corresponding numbers were 86.9% for men and 91.7% for women in Russia (vs 82.2% and 76.8%), for beta-blockers – 82.5 in both genders (vs 80.8% and 81.8%), for ACE inhibitors and/or ARBs 78.0% in men and 80.6% in women (vs 75, 3% and 75.0%). Conclusion: Current prescription of guideline-recommended drug classes in the Russian cohort of EUROASPIRE V survey is close to the average European levels and doesn't demonstrate any obvious gender gaps. However, there is still room for improvement. In particular, this applies to the maintenance of prescriptions made at discharge, especially of statins, in the long term. Funding Acknowledgement: Type of funding sources: None.